Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity. Issue 4 (22nd July 2019) - Karolak, Justyna A.; Szafranski, Przemyslaw; Kilner, David; Patel, Chirag; Scurry, Bonnie; Kinning, Esther; Chandler, Kate; Jhangiani, Shalini N.; Coban Akdemir, Zeynep H.; Lupski, James R.; Popek, Edwina; Stankiewicz, Paweł
Abstract: The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a full‐term newborn, who died at 4 months of age due to progressively worsening PAH and respiratory failure. Family trio exome sequencing showed a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4, both predicted to be likely deleterious. We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct more severe phenotype. Our findings further support a recently proposed complex compound inheritance model in lethal lung developmental diseases and the contention that dual molecular diagnoses can parsimoniously explain blended phenotypes. Abstract : In a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity, who died at 4 months of age due to progressively worsening pulmonary hypertension and respiratory failure, we identified a de novo heterozygous nonsense c.1603C>T (p.Arg535*) variant in CTNNB1 and a paternally inherited heterozygous missense c.1198G>A (p.Glu400Lys) variant in TBX4 . We expand the phenotypic spectrum associated with CTNNB1 and TBX4 variants and indicate that they could act synergistically to produce a distinct severe phenotype.